Implementation of design thinking method in designing consultation booking features on education platforms - Erlin Anggraeni; Ina Maryani; Cindyra Galuhwardani; Saghifa Fitriana (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Education plays a crucial role in developing high-quality, competitive, and adaptive human resources in response to rapid changes. Technology has become indispensable in enhancing the quality and efficiency of learning, but final-year students continue to face difficulties in arranging academic consultations in a flexible manner. This issue can hinder thesis completion and disrupt academic progress. Through this research, a digital solution is proposed by focusing on the design of the user interface (UI) and user experience (UX) for a consultation booking feature on an educational platform. The design thinking process was carried out across five sequential steps: emphatize, define, ideate, prototype, and test. Data were obtained from literautre studies and online surveys, forming the basis for design requirements. Usability testing with 55 users demonstrated that the prototype was generally perceived as easy to operate, effective, and supportive of flexible supervision, yielding an overall satisfaction score of 87.27%. These findings demonstrate that design thinking is effective in producing user-centered digital solutions and highlight the potential of the proposed feature to improve academic support services in higher education.